Study the extent of Rhizobium leguminosarum bv.viciae tolerance to several levels of salinity - Mohammed Altaee (College of Education for Pure Sciences, 2008)
Abstract The effect of different Concentration (1% -5%) of NaCl on growth of Rhizobium leguminosarum bv.viciae was studied by their addition to Manitol yeast extract agar medium and observing the bacterial growth and tolerance to exceeding salt concentration comparing to the control. The bacterium showed higher growth rate than control at 1% concentration, while the rates decreased at other concentration , with no growth at 5% concentration.